A role for brain-specific homeobox factor Bsx in the control of hyperphagia and locomotory behavior - Sakkou, Maria; Ettwiller, Laurence (Cell metabolism, 2007)
Food intake and activity-induced thermogenesis are important components of energy balance regulation. The molecular mechanism underlying the coordination of food intake with locomotory behavior to maintain energy homeostasis is unclear. We report that the brain-specific homeobox transcription factor Bsx is required for locomotory behavior, hyperphagia, and expression of the hypothalamic neuropeptides Npy and Agrp, which regulate feeding behavior and body weight. Mice lacking Bsx exhibit reduced locomotor activity and lower expression of Npy and Agrp. They also exhibit attenuated physiological responses to fasting, including reduced increase of Npy/Agrp expression, lack of food-seeking behavior, and reduced rebound hyperphagia. Furthermore, Bsx gene disruption rescues the obese phenotype of leptin-deficient ob/ob mice by reducing their hyperphagia without increasing their locomotor activity. Thus, Bsx represents an essential factor for NPY/AgRP neuronal function and locomotory behavior in the control of energy balance.